Effect of heat treatments and aggressive media on mechanical properties of porous polytetrafluoroethylene membranes fabricated via electrospinning - Melnik, Evgeniy; Stankevich, Ksenia S.; Zinovyev, Alexey; Poletykina, Ekaterina; Andreev, Artem; Bouznik, Vyacheslav M.; Bolbasov, Evgeny N. (Journal of fluorine chemistry)
Electrospinning is a modern alternative to the expanded method for producing porous polytetrafluoroethylene membranes. High strength and relative elongation, as well as the ability to maintain these properties for a long time when exposed to aggressive media at high temperatures, determine the application scope of the electrospun polytetrafluoroethylene membranes. Herein, we report the effect of Polytetrafluoroethylene/Polyvinyl alcohol ratio in the electrospinning solution, heat treatment mode (quenching and annealing) and aggressive media at high temperatures on the shrinkage, tensile strength and relative elongation of electrospun polytetrafluoroethylene membranes. We found that decreased Polytetrafluoroethylene/Polyvinyl alcohol ratio in the electrospinning solution increases shrinkage, but improves tensile strength and relative elongation of polytetrafluoroethylene membranes. Quenching of membranes after heating is a more preferable treatment option than annealing as it allows to obtain the membrane with less shrinkage and better mechanical properties. Exposure of electrospun polytetrafluoroethylene membranes to concentrated mineral acids and alkalis, a bipolar aprotic solvent, engine oil and deionized water at 100 degrees C for 48 h did not deteriorate their tensile strength and relative elongation.